A Comparative Study of CO Oxidation on Nitrogen‐ and Phosphorus‐Doped Graphene. Issue 17 (7th October 2015) - Esrafili, Mehdi D.; Mohammad‐Valipour, Ramin; Mousavi‐Khoshdel, Seyed Morteza; Nematollahi, Parisa
Abstract: The geometry, electronic structure, and catalytic properties of nitrogen‐ and phosphorus‐doped graphene (N‐/P‐graphene) are investigated by density functional theory calculations. The reaction between adsorbed O2 and CO molecules on N‐ and P‐graphene is comparably studied via Langmuir–Hinshelwood (LH) and Eley–Rideal (ER) mechanisms. The results indicate that a two‐step process can occur, namely, CO+O2 →CO2 +Oads and CO+Oads →CO2 . The calculated energy barriers of the first step are 15.8 and 12.4 kcal mol −1 for N‐ and P‐graphene, respectively. The second step of the oxidation reaction on N‐graphene proceeds with an energy barrier of about 4 kcal mol −1 . It is noteworthy that this reaction step was not observed on P‐graphene because of the strong binding of Oads species on the P atoms. Thus, it can be concluded that low‐cost N‐graphene can be used as a promising green catalyst for low‐temperature CO oxidation. Abstract : A good comparison : The geometry, electronic structure, and catalytic properties of nitrogen‐ and phosphorus‐doped graphene (N‐/P‐graphene) are investigated by DFT calculations. The reaction between adsorbed O2 and CO molecules is studied on both substrates using the Langmuir–Hinshelwood (LH) and Eley–Rideal (ER) mechanisms.